2020
DOI: 10.3390/toxins12110703
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Ulceration and Immune Suppression in Weaned Piglets Associated with Feed-Borne Bacillus cereus and Aspergillus fumigatus

Abstract: As a multifactorial cause, gastric ulceration-mediated diarrhea is widely prevalent in the weaned piglets, impairing pig health and economic benefits. With full implementation of antibiotic stewardship programs in China, Bacillus cereus (B. cereus) and Aspergillus fumigatus (A. fumigatus) were identified frequently in porcine feedstuffs and feeds of the animal industry. Association between feed-borne B. cereus and frequent diarrhea remains unclear. In the present study, we conducted a survey of B. cereus and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…And this trait had drawn much attention to use as microbial nano-factory for metal particle production, which illustrated the booms of the genus in the foregut, whereas B. cereus was strongly inhibited in a similar environment. The intestine of livestock was a natural reservoir for foodborne bacteria, such as B. cereus, which not only caused widely contamination but triggered diarrhea and gastric ulcerations in the piglets, leading to the risk for growth retardation and even death (43,44). Through the antibacterial experiment in vitro, we also found the strong inhibiting effect of S. thermophilus against B. cereus, which also verified the coexclusion effects.…”
Section: Discussionsupporting
confidence: 64%
“…And this trait had drawn much attention to use as microbial nano-factory for metal particle production, which illustrated the booms of the genus in the foregut, whereas B. cereus was strongly inhibited in a similar environment. The intestine of livestock was a natural reservoir for foodborne bacteria, such as B. cereus, which not only caused widely contamination but triggered diarrhea and gastric ulcerations in the piglets, leading to the risk for growth retardation and even death (43,44). Through the antibacterial experiment in vitro, we also found the strong inhibiting effect of S. thermophilus against B. cereus, which also verified the coexclusion effects.…”
Section: Discussionsupporting
confidence: 64%
“…The intestinal mucosal barrier plays an important role as the first barrier against pathogens in defending against harmful external factors and maintaining intestinal health. Impaired intestinal function caused by pathogens will lead to obstructed nutritional absorption [ 3 ], low immunity [ 4 ], and reduced growth performance of pigs [ 5 7 ], causing severe economic losses to the pig industry. Epithelial cells and their tight junctions create a barrier between the external environment and the host.…”
Section: Introductionmentioning
confidence: 99%
“…cereus and other members of the B. cereus group induce two forms of food poisoning: emetic syndrome and diarrheal illness. The emetic (vomiting) syndrome, which is similar to Staphylococcus aureus poisoning, is exacerbated by a ready toxin found in cooked rice and other cereal-based foods that resist high temperatures, trypsin, pepsin, and pH; whereas the diarrheal illness, which is similar to Clostridium perfringens poisoning, In a recent study, it was found that stomach ulceration caused by feed-borne B. cereus in conjunction with severe diarrhea, and co-infection with Aspergillus fumigatus alleviated gastric lesions and immunosuppression in weaned piglets (Li et al 2020).…”
Section: Pathogenesis Of the Diseasesmentioning
confidence: 99%